Comprehensive Analysis to Address the Spread of Tuberculosis - Aung, Theint Myo; San, Min Htun; Khan, Win Latt; Thet, Myint Sein (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
This research explores the elevated incidence of tuberculosis (TB) in Myanmar, where the burden of the disease dramatically surpasses the worldwide average of 500 cases per 100,000 individuals. The research seeks to investigate elements leading to TB prevalence, recognize obstacles to control measures, and suggest practical recommendations. A mixed methods strategy was employed, integrating quantitative information from health statistics in Yangon, Mandalay, and the rural regions of Chin and Shan States with qualitative information gathered from interviews with healthcare professionals and impacted communities. The study results indicate that poverty, malnutrition, limited access to health services, and a lack of awareness are major factors contributing to elevated TB rates, exacerbated by the rise of multidrug-resistant TB (MDR-TB). Insufficient health care systems and cultural prejudices also hinder successful TB management. The research emphasizes the necessity for focused interventions, such as enhancing access to healthcare services, boosting public awareness, and establishing thorough TB screening initiatives. The research highlights the importance of tackling the underlying causes of poverty and malnutrition to lower TB vulnerability. These results have important consequences for expanding TB control initiatives, not just in Myanmar but also in other nations encountering comparable socio-economic issues. Future studies ought to concentrate on assessing the efficacy of the suggested interventions and investigating creative approaches to enhance access to TB treatment while decreasing stigma.